Cortical bone elasticity measured by resonant ultrasound spectroscopy is not altered by defatting and synchrotron X-ray imaging. (August 2017) - Cai, X.; Peralta, L.; Giron, A.; Helfen, L.; Olivier, C.; Peyrin, F.; Laugier, P.; Grimal, Q.
Abstract: In the study of mechanical properties of human bone, specimens may be defatted before experiments to prevent contamination and the risk of infections. High energy synchrotron radiation micro-computed tomography (SR- μ CT) is a popular technique to study bone microstructure. However, little is known about the effects of defatting or irradiation during SR- μ CT imaging on different elastic coefficients including shear and longitudinal moduli in different anatomical directions. In this work, these effects are evaluated on a set of 24 samples using resonant ultrasound spectroscopy (RUS), which allows one to accurately measure the complete set of elastic coefficients of cortical bone non destructively. The results show that defatting with diethylether and methanol and irradiation up to 2.5 kGy has no detectable effect on any of the elastic coefficients of human cortical bone.